Factors influencing innovation capability in The National Institute of Public Administration (INTAN) / Nor Aniza Roslee - Roslee, Nor Aniza (2015)
This research was conducted in order to study the factors influencing innovation in the National Institute of Public Administration (INTAN). This research was study either the variable is related or not. In this research, the researcher was contributed the questionnaire in order to know the either independent variable (Management Support and Trust, Knowledge Sharing, Teamwork, Goal Clarity and Technological Innovation) will give effect on dependent variable which is Innovation Capability. The finding shows that all of variable related each other. The hypothesis testing also show that all hypothesis accepted.